NICKELPHOSPHIDE FROM THE VICENICE OCTAHEDRITE: RIETVELD CRYSTAL STRUCTURE REFINEMENT OF SYNTHETIC ANALOGUE - Skåla R.; Dråbek M. (My University, 2003)
The original description of nickelphosphide from the Butler meteorite [(Ni1.83Fe1.21)Σ3.04P0.96 to (Ni1.71Fe1.28Co0.01)Σ3.00P1.00] lacks detailed and accurate powder data - with only 11 observed reflections down to 1.37 Å. Consequently, no crystal structure information for this phase is available. Here we present the crystal structure for a synthetic analogue of the phase found in the Vicenice IID medium octahedrite (with a mean empirical formula of (Ni1.69Fe1.31)Σ3.00P1.00) and a hypothetical Ni3P end-member. Unit-cell dimensions of the synthetic analogue of Ni1.68Fe1.33P0.99 composition from individual peak profile fitting of XRD data collected with Cu radiation are a = 9.0168(2) Å, c = 4.4491(1) Å, V = 361.72(1) Å3 and those for Ni3P composition are a = 8.9546(1) Å, c = 4.38714(8) Å, V = 351.783(8) Å3. The space group of the mineral is I4¯and Z = 8. The crystal structure refined from powder data by the Rietveld method is consistent with that refined and published for Fe3P and Ni3P synthetic compounds as well as Fe-dominant schreibersite from single-crystal data. However, because of the similarity of the scattering of iron and nickel, we were not able to refine directly the site occupancies in the synthetic analogue of the nickelphosphide from the Vicenice iron meteorite.
Keywords: nickelphosphide; Vicenice; Rietveld reﬁnement; crystal structure; iron meteorites